Extended interval dosing of natalizumab in multiple sclerosis. Issue 8 (25th February 2016) - Zhovtis Ryerson, L; Frohman, T C; Foley, J; Kister, I; Weinstock-Guttman, B; Tornatore, C; Pandey, K; Donnelly, S; Pawate, S; Bomprezzi, R; Smith, D; Kolb, C; et al.
Abstract : Background: Natalizumab (NTZ), a monoclonal antibody to human α4 β1 /β7 integrin, is an effective therapy for multiple sclerosis (MS), albeit associated with progressive multifocal leukoencephalopathy (PML). Clinicians have been extending the dose of infusions with a hypothesis of reducing PML risk. The aim of the study is to evaluate the clinical consequences of reducing NTZ frequency of infusion up to 8 weeks 5 days. Methods: A retrospective chart review in 9 MS centres was performed in order to identify patients treated with extended interval dosing (EID) regimens of NTZ. Patients were stratified into 3 groups based on EID NTZ treatment schedule in individual centres: early extended dosing (EED; n=249) every 4 weeks 3 days to 6 weeks 6 days; late extended dosing (LED; n=274) every 7 weeks to 8 weeks 5 days; variable extended dosing (n=382) alternating between EED and LED. These groups were compared with patients on standard interval dosing (SID; n=1093) every 4 weeks. Results: 17% of patients on SID had new T2 lesions compared with 14% in EID (p=0.02); 7% of patients had enhancing T1 lesions in SID compared with 9% in EID (p=0.08); annualised relapse rate was 0.14 in the SID group, and 0.09 in the EID group. No evidence of clinical or radiographic disease activity was observed in 62% of SID and 61% of EID patients (p=0.83). No cases of PML were observed in EID group compared with 4 cases in SID cohort. Conclusions: Dosing intervals up to 8 weeks 5 days did not diminish effectiveness of NTZ therapy. Further monitoring is ongoing to evaluate if the risk of PML is reduced in patients on EID.